PROBLEMATIKA TUMPANG TINDIH SERTIFIKAT KEPEMILIKAN TANAH DI KABUPATEN KUTAI KARTANEGARA BERDASARKAN UNDANG-UNDANG NOMOR 5 TAHUN 1960 TENTANG PERATURAN DASAR POKOK-POKOK AGRARIA - Faizal Faizal (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACTThe legal certainty of land rights is sometimes not guaranteed as expected. Practice in the field is not uncommon for the circulation of fake certificates, genuine certificates but fake or overlapping certificates in the community so that land rights holders need to find information about the truth of physical and juridical data on certain parcels of land at the local Land Office. In general, new problems arise and it is known that the issuance of certificates of land overlaps, when the holder of the certificate concerned will carry out a legal action on the intended parcels of land.The type of research the author uses is Normative legal research. Normative Legal Research (normative juridical) is a legal research method carried out by examining mere library materials or secondary data.The results of the study stated that the factors causing the issuance of overlapping ownership certificates / overlapping in Kutai Kartanegara Regency based on Law Number 5 of 1960 Regarding Local Regulation on Agrarian Principles is the Error of the land owner himself who does not pay attention to his land and does not use it so well that it is taken over by another person. When measuring or researching in the field, the applicant intentionally or unintentionally shows the location of the land and the wrong land boundary, as well as the intentions of the land owner to re-register the certificate that actually already exists by utilizing the weaknesses of the institution National Land Agency. Efforts of the Land Office of Kutai Kartanegara Regency in resolving land disputes over the issuance of overlapping ownership certificates / overlapping in Kutai Kartanegara Regency based on Law Number 5 of 1960 Concerning Local Agrarian Regulations with deliberations or mediation conducted outside the court with or without mediators . If the settlement is also not reached, then you are welcome to file a lawsuit through the State Administrative Court.Keywords: Multiple, Dispute, Land